Obstructive sleep apnea in chronic kidney disease patients undergoing hemodialysis. Prevalence, severity, and treatment. A narrative review - Antônio Calixto de Pina Gomes Mello, Diego; dos Reis dos Santos, Israel; Roberta Danaga, Aline; Pedro Ribeiro Afonso, João; Silva Moura, Ricardo; Cândida Oliveira, Miriã; Nobrega da Silva Nunes, Carla; Arantes Souza, Shayra Kellen; Martins Rodrigues Silva, Bruna; Silva Souza, Max; Fernandes Oliveira, Ezequiel; Carlos Queiroz, Bruno; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Chronic kidney disease (CKD), also known as chronic renal insufficiency (CRI), can be defined by a glomerular filtration rate (GFR) less than 60mL/min/1.73m^2 associated with an albumin-to-creatinine ratio greater than 30mg of albumin per 1g of creatinine. CKD is a significant factor leading to a decline in the quality of life, increased morbidity, and a substantial reduction in life expectancy. Currently, it is estimated that there are 3.9 million patients worldwide on renal replacement therapy for CKD. Recent data indicates that in the United States of America (USA), more than 500,000 people suffer from renal failure or insufficiency. In Brazil, epidemiological data is incomplete and outdated. In 2016, there were 122,825 patients in Brazil on renal replacement therapy. Objectives: This literature review aims to assess the prevalence, severity, and therapeutic recommendations for obstructive sleep apnea (OSA) in patients with CKD undergoing hemodialysis. Methods: A literature review was conducted using PubMed, Web of Science, and SciELO databases with keywords including "Obstructive Sleep Apnea", "Chronic kidney disease", "End-stage renal disease", "sleep disorders", "hemodialysis", "CPAP", "Continuous positive airway pressure", and "Physiotherapy." Only studies published in the last twenty years and in the English language were included. Results: Despite scientific evidence demonstrating a high prevalence of OSA in CKD patients undergoing hemodialysis, there are still a lack of studies examining the effects of Continuous positive airway pressure (CPAP) therapy on the clinical outcomes of these patients. In the scientific literature, only three randomized clinical trials were found that investigated the impact of CPAP therapy on improving kidney function. Consequently, there is a critical need for clinical studies to assess the effects of CPAP therapy in CKD patients undergoing hemodialysis. It is also essential to highlight the role of physiotherapy in managing sleep disorders and aiding in the adaptation and monitoring of patients undergoing CPAP therapy. Conclusion: This literature review concluded that more randomized controlled studies are necessary to better define the optimal therapy for OSA in CKD patients, with the goal of preventing a decline in GFR progression, reducing morbidity and mortality, and enhancing overall quality of life.